Efektivitas Penggunaaan Aplikasi PLN Mobile Di Tinjau Dari Perilaku Keuangan Dan Kualitas Layanan Pada PT. PLN (Persero) UP3 Padang - Ramadonal .; Henny Sulistianingsih (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
This study aims to analyze the effectiveness of the PLN Mobile application at PT. PLN (Persero) UP3 Padang, evaluated through the lenses of Electronic Service Quality (E-Service Quality) and Financial Behavior. The research employs a quantitative method utilizing Variance-based Structural Equation Modeling (SEM-PLS) via SmartPLS, with a sample of customers residing in the UP3 Padang area. The results indicate that E-Service Quality has a positive and significant impact on both application effectiveness and customer financial behavior. Furthermore, Financial Behavior is proven to mediate the relationship between service quality and the overall effectiveness of the application. Based on the Respondent Achievement Level (TCR) criteria, the PLN Mobile application is categorized as [Very Good/Good]. Managerial implications of this research emphasize the importance of enhancing system stability and digital financial literacy education to increase transaction penetration within the application.